INVARIANT FEATURES OF PERSONAL IDENTITY AND THE PROCESS OF ITS FORMATION: THE PEDAGOGICAL CONTEXT - Selivanova, Natalia; Sklyarova, Tatjana; Shakurova, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Research objective: pedagogical judgment of intrinsic and remedial bases of development and formation of identity of the person, allocation педагогически significant invariant characteristics. Novelty consists in statement of a question, ordering of results of researches of identity with accent of pedagogical senses, use of the interdisciplinary approach. The developed analysis significant from the point of view of pedagogics of characteristics of identity is given: concept definitions through specification of separate displays of essence, allocation of levels (socially-cultural identity, personal identity, self-identity) and kinds (by criterion of substantial filling). Possibility of the pedagogical organized influence on formation of socially-cultural and personal identity and impossibility of work by pedagogical means with self-identity is accented. The characteristic of kinds of identity of the person, as by this time only studied by the Russian pedagogics (cultural, ethnic, professional, gender, religious), and already included in a purpose of modern Russian education (civil identity, the Russian civil identity) is given. The interrelation of various kinds of identity (on an example of the Russian civil and religious identity) is shown. The leading condition of formation of high-grade identity (unity of self-determination, definition by Others and Another's) is illustrated. Distinction in understanding of designs «development of identity of the person» and «formation of identity of the person» is accented, the attention to pedagogical expediency of studying, the organization and technological working out of process of formation of identity of the person is paid. Invariant pedagogical mechanisms of process of formation of identity of the person are allocated and is short characterized: pedagogical interaction; formation of the importance and work with the significant; pedagogical support.